The Role of the Members of «Prosvita» Society in the Organization of the Church Congresses on the Territory of Volyn Region During 20–30-ies of the 20th Century - Petrovych, Valentina; Charikova, Iryna; Петрович, Валентина; Чарікова, Ірина (My University, 2016)
The article highlights the role of the members of ««Prosvita»» society in the development of the national and church movement on the territory of Volyn region during 20–30-ies of the 20th century, aimed at the democratization and ukrainization of the church and religious life. The importance of the church congresses for the resurgence of the Ukrainian Orthodox Church in Poland was investigated.У статті проаналізовано процес українізації церковного устрою в контексті розвитку національно- церковного руху української православної громади Волині у 20-30-х рр. ХХ ст. На підставі урахування суспільно- політичних, етноконфесійних, внутріцерковних та регіональних особливостей доводиться, що національно- церковний рух на Волині міжвоєнного періоду взаємопов’язаний із якісним процесом національної ідентифікації українського народу.
Участь просвітян в організації церковних з’їздів на Волині у 20- 30-х рр. ХХ ст.
Keywords: church congress; national and church movement; «Prosvita»; ukrainization; Orthodox Church; церковний з’їзд; національно-церковний рух; «Просвіта»; українізація; православна церква; Арсен Річинський